Non-metal modified TiO2: a step towards visible light photocatalysis - Mittal, Anuj; Mari, Bernabe; Sharma, Shankar; Kumari, Vijaya; Maken, Sanjeev; Kumari, Kavitha; Kumar, Naveen (Journal of materials science. Materials in electronics, 2019)
Advanced oxidation process (AOP) is a versatile photocatalytic approach to degrade various environmental pollutants. Among many photocatalysts used in AOP such as ZnO, TiO 2 , ZrO 2 , ZnS, CdS; TiO 2 is the most widely adopted semiconductor material. TiO 2 is a wide band gap material and absorb in UV spectrum which is a narrow region in the sun light. This benchmark makes it a less efficient photocatalyst under sunlight irradiation. To enhance the photocatalytic efficiency, the absorption band of photocatalyst should be modified in such a way that it leads to maximum absorption in the solar spectrum. The doping of nonmetals such as N, C, P and S etc. shift the band edge of the semiconductors towards the visible region and thus increases the photon absorption which successively enhances the photocatalytic efficiency. In this review, we have focused on effect of nonmetal doping on the properties and photocatalytic activity of the TiO 2 . Influence of various aspects such as synthesis procedure, doping source, concentration of dopant, calcination etc. are also explored towards alteration in properties and photocatalytic efficiency of nonmetals doped TiO 2 .